2022
DOI: 10.3390/antiox11071350
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen Interferes with Alzheimer’s Disease by Regulating Mitochondrial Function

Abstract: (1) Background: With unknown causes and no effective treatment available, Alzheimer’s disease (AD) places enormous pressure on families and society. Our previous study had shown that Ebselen at a high concentration (10.94 μM) improved the cognition of triple-transgenic AD (3×Tg-AD) mice and alleviated the related pathological indicators but showed toxicity to the mice. Here, we dedicated to study the therapeutic effect and molecular mechanism of Ebselen at a much lower concentration on 3×Tg-AD mice. (2) Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…56 However, multiple studies have demonstrated that selenium can protect mitochondrial function by upregulating mitochondrial biogenesis. 46,57–60 In the present research, after SMC treatment, AKT was activated and the levels of Nrf1, Nrf2 and mtTFA in AD models were increased (Fig. 3).…”
Section: Discussionsupporting
confidence: 60%
“…56 However, multiple studies have demonstrated that selenium can protect mitochondrial function by upregulating mitochondrial biogenesis. 46,57–60 In the present research, after SMC treatment, AKT was activated and the levels of Nrf1, Nrf2 and mtTFA in AD models were increased (Fig. 3).…”
Section: Discussionsupporting
confidence: 60%
“…MitoEbselen demonstrates potent antioxidant activity and has been observed to preserve cell function during oxidative stress in many cell types and disease models, including cardiovascular disease [ 41 ]. Furthermore, H 2 O 2 scavenging by MitoEbselen has been seen to positively influence OCR and mitochondrial function in multiple cell types, including endothelial cells [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic, sustained increases in H 2 O 2 can negatively impact mitochondrial functioning and OCR. Therefore, H 2 O 2 scavenging by MitoEbselen has been seen to positively influence OCR and mitochondrial function in multiple cell types, including endothelial cells [ 42 , 43 ]. Notably, MitoEbselen treatment does not further increase OCR in Ng overexpression HAECs, which hints that a different pathway may become dominant in endothelial cells when Ng is overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence have demonstrated that amelioration of mitochondrial homeostasis to restore the normal function of mitochondria is beneficial for the prevention or treatment of AD (Li et al 2022c ; Li et al, 2022b ). Thus, whether Trx-1 regulates mitochondrial homeostasis in AD was further investigated.…”
Section: Discussionmentioning
confidence: 99%